Computer prediction of technological modes of rapid cone-shaped adsorption filters with automated discharge of part of heat from separation surfaces in filtering mode - Klymiuk, Yurii; Bomba, Andrii (Моделювання, керування та інформаційні технології, 2021)
In the paper a mathematical models of technological modes of filtration with automated removal of part of heat from interface surfaces (water purification from multicomponent impurities), backwashing, chemical regeneration and direct washing of rapid cone-shaped adsorption filters with chemical regeneration of piecewise homogeneous porous loads while maintaining constant velocities of the respective modes is formulated. The proposed models in the complex allow to conduct computer experiments to investigate the change in the concentrations of components of a multicomponent impurity in the filtration stream and on the surface of the loading adsorbent, retained by both physical and chemical adsorption, filtration flow temperature, filtration coefficient, active porosity and pressure along the filter height and on their basis to predict more optimal options for the use of adsorbents of each loading layer and increase the protective time of rapid cone-shaped adsorption filters with automated heat removal from the interface surfaces in filter mode.